Arthritis is associated with an increased risk of incident diabetes in Chinese adults: A nationwide cohort study and updated meta‐analysis. Issue 2 (3rd August 2021) - Yang, Xue; Xie, Yue; Wang, Yi; Yu, Yong; Jin, Xingzhong; Xiu, Peng; Wu, Jason H. Y.; Yu, Danxia; Pan, An; Zhao, Jian; Yang, Chun‐Xia; Pan, Xiong‐Fei
Abstract: Aims: To prospectively examine the association between arthritis and type 2 diabetes (T2D) in the Chinese population and confirm this association through a comprehensive meta‐analysis of cohort studies. Meterials and Methods: Data were from the China Health and Retirement Longitudinal Study which was started in 2011–2013 and followed up in 2013–2014 and 2015–2016. Arthritis was defined as self‐reported physician diagnosis at baseline, and incident T2D was determined by self‐reported physician diagnosis, fasting blood glucose ≥7.0 mmol/L or glycosylated haemoglobin ≥6.5% during the follow‐ups. Cox proportional hazards regression models were used to assess the association between arthritis and risk for T2D. A meta‐analysis was conducted to pool our effect estimate and those from other cohort studies using a random‐effects model. Results: Eleven thousand four hundred and eight participants (47.9% men; mean age: 59.3 years) were included in final analyses. During a 4‐year follow‐up, 981 participants reported incident T2D. Compared with individuals without arthritis, those with arthritis at baseline had an 18% higher risk for incident T2D (multivariable‐adjusted hazard ratio: 1.18; 95% confidence interval: 1.04, 1.34). In the meta‐analysis of 13 cohort studies including ours, a total of 2, 473, 514 participants were included with 121, 851 incident diabetes. The pooling HR was 1.32 (95% CI: 1.21, 1.44) for the association between arthritis and diabetes. Conclusion: Arthritis was associated with an increased risk of incident diabetes in Chinese adults, and the positive association was confirmed in the meta‐analysis of cohort studies. Our work can inform clinical trials to assess the effectiveness of arthritis treatments in reducing risk of diabetes.